Cultivating Elementary Students Creative Thinking In Science Through Project Based Learning: Menumbuhkan Keterampilan Berpikir Kreatif Siswa Sekolah Dasar Melalui Pembelajaran Berbasis Proyek - Khoiriah, Isti Nganatul; Subhanadri, Subhanadri; Habibie, Zulqoidi R (Academia Open, 2026)
General Background The rapid changes of the Industrial Revolution 4.0 demand that students possess high-order cognitive abilities, particularly the capability to generate new ideas and solve real-world problems. Specific Background Natural and Social Sciences subjects in elementary education provide an ideal context for fostering these cognitive traits, yet conventional teacher-centered instructional methods often result in passive learning environments and suboptimal student participation. Knowledge Gap Although previous studies acknowledge the benefits of active educational frameworks, research specifically examining the developmental trajectory of fluency, flexibility, originality, and elaboration within contextual science tasks for fifth-grade students remains limited. Aims This study analyzes the application of a contextual instructional model to cultivate the cognitive abilities of fifth-grade students in science subjects at SD Negeri 49/II Senamat. Results Utilizing a quantitative pre-experimental one-group pretest-posttest design with 20 students, the analysis revealed a significant score increase from a pre-test average of 72.75 to a post-test average of 79.50. A paired sample t-test yielded a significance value of 0.000, confirming the positive statistical outcome. Novelty This research distinctly maps the progression of four specific ideation indicators during practical science tasks, extending beyond general achievement metrics. Implications Educational practitioners should adopt contextual problem-solving models to transform passive classrooms into dynamic, student-centered environments that actively train future generations in complex ideation. Highlights Contextual instructional frameworks significantly elevate ideation indicators, including fluency, flexibility, originality, and elaboration capabilities. Implementing active problem-solving activities increases the average pupil performance score from 72.75 to a final post-test outcome of 79.50. Transforming teacher-centered instruction into practical exploration effectively mitigates passive classroom participation. Keywords Contextual Problem Solving; Active Learning Environments; Cognitive Ability Development; Elementary Science Education; Higher Order Thinking